PENERAPAN KONSEP PERILAKU PADA PERANCANGAN LEMBAGA PEMASYARAKATAN WANITA IIA DI BANDA ACEH - Muhammad Iqbal (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
AbstractThe number of wickedness or criminality in the developing countries keep increasing every year. The Society Institution is a place of tutoring for perpetrators of criminal to be fostered in order to return back to the community. There are few differences  method of teaching applied between men and woman. Therefore the needs of place for Society institution as the corresponds is to have a place for each type. The number of Crime in Banda Aceh is getting higher each year, but they do not have any Society Institution for woman yet. There are some processes needed before designing the Woman Society Institution by applying the characteristics type of space and building according to the behavior of the perpetrators. The theme is “Behavior Architecture”, with collaborating the behavior of the user and the standard of secure system to make the process of tutoring the perpetrators much better. So the result from this Society Institution can create new face and perception as Institution with great role in obtaining the final aim of the Society Institution System, which are the rehabilitation and resocialization of law offenders, and crime prevention.  Keys : Society institution, prisoner, coaching, woman, behavior